SPATIAL VARIABILITY AND SAMPLING DENSITY OF MAGNETIC SUSCEPTIBILITY AND SOIL PROPERTIES IN ULTISOLS OF THE MANICORE REGION, AM, BRAZIL - Oliveira, Ivanildo Amorim de [UNESP]; Marques Junior, Jose [UNESP]; Costa Campos, Milton Cesar; Aquino, Renato Eleoterio de [UNESP]; Freitas, Ludmila de [UNESP]; Siqueira, Diego Silva [UNESP]; Cunha, Jose Mauricio da (Soc Brasileira De Ciencia Do Solo, 2015)
The difficulty in finding recent information on the spatial behavior of properties of soils in the Brazilian Amazon region has been a concern of many researchers. Due to the great difficulty and costs in assessing soil properties, alternative methods have been used for prediction, such as magnetic susceptibility. Thus, the objective of this study was to evaluate the spatial variability of magnetic susceptibility and of physical and chemical soil properties in an Argissolo Vermelho (Ultisol) from native forest, Archaeological Black Earth under cultivation, and pasture in the region of Manicore, Amazonas. Grids of 70 x 70 m were established in these areas, demarcating points at a regular 10 x 10 m spacing, for a total of 64 points. These points were georeferenced, and then soil samples were taken at each point of the grid in the 0.00-0.20 and 0.40-0.60 m layers for determination of chemical properties (pH in water, organic matter, P, K, Ca, Mg, and potential acidity), physical properties (texture, macroporosity, microporosity, weighted mean diameter, bulk density, and particle density), and magnetic susceptibility. The data were subjected to analysis of variance, and mean values were compared by the Tukey test at 5 %. Descriptive statistics were carried out, as well as geostatistics with the use of scaled semivariograms, for characterization of variability. The range of the scaled semivariograms was used to determine the minimum sampling density to estimate the variability of the properties under study. The area of Archaeological Black Earth and pasture exhibited greater variability, with a lower range and higher sampling density (five points per hectare). Magnetic susceptibility exhibited spatial behavior similar to the physical and chemical properties studied, with the magnetic susceptibility sampling density near the sampling density of the soil properties in the environments under study.
Keywords: geostatistics; Archaeological Black Earth; scaled semivariogram